2015
DOI: 10.1515/ract-2015-2436
|View full text |Cite
|
Sign up to set email alerts
|

An in-situ X-ray absorption spectroelectrochemical study of the electroreduction of uranium ions in HCl, HNO3, and Na2CO3 solutions

Abstract: A spectroelectrochemical cell was fabricated for in-situ X-ray absorption spectroscopy (in-situ XAS). The XAS spectra of the uranium III edge were monitored in electrolyte solutions during the electrochemical reduc-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The coordination number was assumed to be U-O ax = 2 and the bond distance was determined to be in the range 1.76-1.82 Å (Table 2). These results were in agreement with a previous report of the inter-atomic distances in U-O ax (Uehara et al, 2016)…”
Section: Xafs Analysis Of Comparative Samplessupporting
confidence: 94%
See 2 more Smart Citations
“…The coordination number was assumed to be U-O ax = 2 and the bond distance was determined to be in the range 1.76-1.82 Å (Table 2). These results were in agreement with a previous report of the inter-atomic distances in U-O ax (Uehara et al, 2016)…”
Section: Xafs Analysis Of Comparative Samplessupporting
confidence: 94%
“…3(a)] were slightly narrower. It was previously demonstrated that the edge jump for uranium (IV) shifts slightly to lower energy and the peak widths decrease compared with those of uranium (VI) (Kalkowski et al, 1986;Uehara et al, 2016). Our results indicate the possible presence of small amounts of uranium mixed chemical forms, although most of the uranium accumulated in kidney was hexavalent UO 2 2+ at all toxicological phases, irrespective of the age of the rat.…”
Section: Xafs Analysis Of Bulk Rat Kidneysupporting
confidence: 53%
See 1 more Smart Citation
“…Most of the uranium that accumulated in the kidneys was uranium (VI), but some had an edge that slightly shifted towards lower energy, meaning that uranium was reduced after administration [16]. The reduction of uranium (VI) to (V) or (IV) results in a slight shift of the edge jump at 1–2 eV and a slight narrower peak [17,18], indicating that the proximal tubules without concentrated phosphorus could contain chemical forms of uranium that varied between (VI) and a reduced form. Further examinations with several reduced standards and improved spectral quality are needed to clarify the formation of the reduced form of uranium.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that over 10 times of scanning is necessary to obtain a clear edge jump of the spectra, although the background noise is not negligible compared to that obtained with at less than two times of scanning. Curves 1 and 3 refer to the spectra of U(VI) in serum containing 0.5 mM uranyl acetate and U(IV) in 1 M HCl which was prepared by electrochemical reduction 46 as different valence status of U. Furthermore, the white line of curve 2 appears to resemble close to that of curve 1, indicating that the valence of U in the serum collected from rats is hexavalent.…”
Section: Xas Measurements Of U In Serum In the Absence Of Chelating A...mentioning
confidence: 99%